Evaluation of echocardiographic parameters in patients of acute right ventricular myocardial infarction and its association with in-hospital outcome - Anubhav Prakash; Pradip Saha; Pradip Kumar Ghoshal; Goutam Datta; Saroj Mondal; Abhisek Naskar; Bablu Nandi (Asian Journal of Medical Sciences, 2025)
Background: This study investigates the role of various echocardiographic parameters in assessing right ventricular (RV) function in patients with inferior wall myocardial infarction (IWMI) and RV myocardial infarction (RVMI). Aims and Objectives: The primary objective is to evaluate the use of pulmonary regurgitation pressure half-time (PRPHT) and RV global longitudinal strain (RVGLS) as indicators of RV dysfunction and prognostic markers for adverse in-hospital outcomes and the outcome at 3 month follow-up. Materials and Methods: The study is a prospective observational cross-sectional analysis conducted at the public sector apex institute in eastern India, involving 155 patients diagnosed with acute IWMI/RVMI. Patients underwent a comprehensive echocardiographic evaluation and management, followed by a 3-month post-treatment follow-up. Results: The findings suggest significant correlations between echocardiographic parameters of RV function. It was noted that patients with PRPHT values <90, tricuspid annular plane systolic excursion (TAPSE) of <10, FAC of <28%, and RVGLS value of <(−12) were able to predict in-hospital outcome in patients of IWMI/RVMI. The findings of the present study also suggest that interventions in IWMI/RVMI have good outcomes at 3-month follow-up. Conclusion: The results also indicate that PRPHT could serve as a valuable prognostic indicator in patients with PRPHT ≤100 m. It was noted that RVGLS bears no value in predicting in-hospital outcomes. The study concludes that integrating PRPHT with traditional markers viz. TAPSE, RVFAC, and RVGLS provide a comprehensive assessment of RV function, enabling better identification of patients at risk of adverse outcomes following IWMI/RVMI.